Growing blood vessels in space: Preparation studies of the SPHEROIDS project using related ground-based studies. (June 2019) - Krüger, Marcus; Kopp, Sascha; Wehland, Markus; Bauer, Johann; Baatout, Sarah; Moreels, Marjan; Egli, Marcel; Corydon, Thomas J.; Infanger, Manfred; Grimm, Daniela
Abstract: Endothelial cells (ECs) grow as single layers on the bottom surface of cell culture flasks under normal (1 g ) culture conditions. In numerous experiments using simulated microgravity we noticed that the ECs formed three-dimensional, tube-like cell aggregates resembling the intima of small, rudimentary blood vessels. The SPHEROIDS project has now shown that similar processes occur in space. For the first time, we were able to observe scaffold-free growth of human ECs into multicellular spheroids and tubular structures during an experiment in real microgravity. With further investigation of the space samples we hope to understand endothelial 3D growth and to improve the in vitro engineering of biocompatible vessels which could be used in surgery. Highlights: EA.hy926 is the most suitable endothelial cell line cell line for space experiments. EA.hy926 cells form tube-like aggregates in space similar to experiments in s-μ g . Key proteins of endothelial spheroid formation build an interaction network. OPN, LOX, and HMOX were up-regulated; IFIT1, IFI44L, MX1 were down-regulated in μ g . The RPM can used for endothelial tissue engineering.